Do Women Shy Away From Competition? Do Men Compete Too Much? - Niederle, M.; Vesterlund, L. (Quarterly Journal of Economics, 2007)
We examine whether men and women of the same ability differ in their selection into a competitive environment. Participants in a laboratory experiment solve a real task, first under a non-competitive piece rate and then a competitive tournament incentive scheme. Although there are no gender differences in performance, men select the tournament twice as much as women when choosing their compensation scheme for the next performance. While seventy-three percent of the men select the tournament only thirty-five percent of the women make this choice. This gender gap in tournament entry is not explained by performance and factors such as risk and feedback aversion only play a negligible role. Instead the tournament-entry gap is driven by men being more overconfident and by gender differences in preferences for performing in a competition. The result is that women shy away from competition and men embrace it. * We thank Scott Kinross, who conducted all the experiments reported in this paper, for his excellent research assistance. We thank the editors and the referees who helped us improve the paper. We also